IMPLEMENTASI PENDEKATAN ETNO-STEM BERBASIS PROYEK DI ERA KURIKULUM MERDEKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN BERPIKIR KRITIS MATEMATIS - Putri, Emilia; Anggoro, Bambang Sri; Muhammad, Rosida Rakhmawati (De Fermat : Jurnal Pendidikan Matematika, 2026)
The Merdeka Curriculum currently implemented in Indonesia strongly supports the development of 21st-century skills, particularly creative and critical thinking abilities. However, based on the 2022 PISA data, Indonesian students’ creative and critical thinking skills are still below the OECD average, indicating the need for active and contextual learning. This study aims to investigate the effect of a project-based Etno-STEM approach on improving students’ mathematical creative and critical thinking skills. This research employed a quasi-experimental method with a non-equivalent control group design involving experimental and control classes with pre-test and post-test. The population of this study consisted of eleven eighth-grade class at SMPN 2 Bandar Lampung. The sample was selected using a simple random sampling technique, with class VIII.6 consisting of 34 students as the control class, and classes VIII.7 and VIII.11 consisting of 32 and 31 students respectively as the experimental classes. Data were collected through tests of mathematical creative and critical thinking skills, supported by observations and documentation. The data were analyzed using Multivariate Analysis of Variance (MANOVA) and N-Gain.The results show that the project based Etno-STEM approach has significant effect on improving students’mathematical creative and critical thinking skills.